PROPHET MUHAMMAD SAW'S HIJRAH EVENTS TO YASTRIB - Yuyun Yunita; Abdul Mujib (An Najah (Jurnal Pendidikan Islam dan Sosial Keagamaan), 2022)
The migration of the Prophet Muhammad SAW. concludes that da'wah and aqidah will be able to free a person from everything he loves from all friends, companions, entertainers, and all the things that are given; of every priority, held firmly and obeyed, according to its original character. On the other hand, everything will not be able to release da'wah and creed from humans. The history of da'wah and religion has been side by side with movements that are sometimes independent and sometimes together. There are several backgrounds to the events of the migration of the prophet Muhammad SAW. Among them are: the death of two proselytizing figures, torture of Muslims, the Quraysh leadership will kill the prophet, Bai'ah Aqabah, opposition to da'wah in Mecca, the failure of the call for Islam in Taqif, many Muslims in Medina , the people of Medina easily accept Islamic teachings, and the strategic location of Medina.